Ultrasonographic investigation of the Achilles tendon in elite badminton players using color doppler - Ilum Boesen, M.; Boesen, A.; Juhl Koenig, M.; Bliddal, H.; Torp-Pedersen, S. (The American Journal of Sports Medicine, 2006)
The most frequent injuries in badminton players are in the lower extremities, especially in the Achilles tendon.